Field notes contributed by Mike Brown, summer 1984 - Brown, Mikeet al (1984)
Field notes were contributed by Mike Brown, summer 1984. Birds sighted were a Short-eared Owl, Double-crested Cormorant, and Ring-necked Duck, as well as a Virginia Rail nest and a Canada Geese brood. Locations included Stony Lake, Dickinson County, Union Slough and Yager Slough. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1984. Epson - sheet feed/flatbed